Rescuing Arbitration in the Developing World the Extraordinary Case of Georgia - Steven Austermiller (Alternative Dispute Resolution Yearbook, 2016)
The country of Georgia has a long and interesting history with arbitration. From “telephone justice” to the criminal underworld to legitimacy, Georgian arbitration has survived many iterations. Now, as Georgia begins the EU accession process, it has a new arbitration law that incorporates international norms. This article analyzes the law, explores how arbitration has been implemented thus far, and discusses some of the challenges that remain. Drawing on his U.S. practice experience in arbitration and his work managing legal reform programs in Georgia and other countries, the author recommends some important changes to Georgia’s new arbitration regime. A particular area of concern is the use of mandatory consumer arbitration in firms’ standard form contracts. With some adjustments, arbitration in Georgia can become a model for other developing countries, balancing the commercial needs of firms with the justice and social needs of Georgian society. The author concludes that with his recommendations, other developing countries can learn from this experience and use arbitration to promote efficiency and investment, while safeguarding individuals’ rights.